Volatile metabolomics and coexpression network analyses provide insight into the formation of the characteristic cultivar aroma of oolong tea (Camellia sinensis). (15th July 2022) - Zheng, Yucheng; Hu, Qingcai; Wu, Zongjie; Bi, Wanjun; Chen, Bin; Hao, Zhilong; Wu, Liangyu; Ye, Naixing; Sun, Yun
Abstract: Finished oolong tea products with distinctly characteristic cultivar aromas generally have higher economic value. To advance our understanding of the aromatic differences between Camellia sinensis cv. Tieguanyin (TGY) and Jinguanyin (JGY) cultivars and their underlying formation mechanism, volatile metabolomics analysis, electronic nose (EN) analysis, sensory evaluation, and RNA sequencing were performed during this study. The EN and sensorial analysis showed a significant difference in odour characteristics between the two cultivars, which featured sweet floral and fruity aromas and green floral aromas, respectively. A metabolomics analysis of tea products showed that linalool (floral, OAV = 50.6) and geraniol (rose-like and sweet, OAV = 1.9) may contribute to the characteristic aroma. The volatile determination at each stage during the oolong tea manufacturing process emphasized that the significant difference in linalool and geraniol contents in fresh leaves from the two cultivars and the increase rate were potential reasons for their characteristic aroma and suggested that the "Tanqing" treatment clarified and intensified the characteristic cultivar aroma. A linalool synthase CsLIN with the expected catalytic activity was identified by coexpression network analyses. Collectively, our work pinpoints two key aroma substances within two cultivars and elaborates on the potential cause of characteristic cultivar aroma formation. Graphical abstract: Image 1 Highlights: Linalool and geraniol contribute to the characteristic cultivar aroma. Different increase rates of key volatile during processing leads to cultivar aroma. Tanqing treatment clarifies and intensifies the characteristic cultivar aroma. A linalool synthase CsLIN with the expected catalytic activity was identified.